2020
DOI: 10.1182/bloodadvances.2019000984
|View full text |Cite
|
Sign up to set email alerts
|

Five-year results of the BEGEV salvage regimen in relapsed/refractory classical Hodgkin lymphoma

Abstract: The complete remission (CR) rate achieved with induction chemotherapy prior to autologous stem cell transplantation (ASCT) represents the strongest prognostic factor in relapsed/refractory (R/R) classical Hodgkin lymphoma (cHL). By inducing a CR rate of 75%, the bendamustine, gemcitabine, vinorelbine (BEGEV) regimen represents an optimal chemotherapy regimen prior to ASCT. Presented here are the 5-year results of BEGEV followed by ASCT in R/R cHL. With a median follow-up of 5 years, progression-free survival (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 21 publications
1
22
0
5
Order By: Relevance
“…4,5 More recent studies show considerably better outcomes for rel/ref disease with a 2-year progression-free survival (PFS) of about 70% or better. 6,7 Two main factors account for the improved outcomes observed in recent studies: the We previously reported that the 5-year event-free survival for rel/ref cHL patients with negative pre-HDT/AHCT functional imaging (gallium or FDG-PET) was 75% compared with 31% for patients with persistent abnormalities on functional imaging. 8 Numerous other groups reported similar findings, suggesting that normalization of FDG-PET following SLT should be a goal for patients proceeding to HDT/AHCT.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 More recent studies show considerably better outcomes for rel/ref disease with a 2-year progression-free survival (PFS) of about 70% or better. 6,7 Two main factors account for the improved outcomes observed in recent studies: the We previously reported that the 5-year event-free survival for rel/ref cHL patients with negative pre-HDT/AHCT functional imaging (gallium or FDG-PET) was 75% compared with 31% for patients with persistent abnormalities on functional imaging. 8 Numerous other groups reported similar findings, suggesting that normalization of FDG-PET following SLT should be a goal for patients proceeding to HDT/AHCT.…”
Section: Introductionmentioning
confidence: 99%
“…Полученные результаты согласуются с данными международных исследований по применению ре жимов с оригинальным бендамустином [5,6,9] и под черкивают высокую эффективность и хороший мо билизационный потенциал Розустина ® . Результаты гематологической и негематологической токсичности в целом также соответствуют данным литературы по применению Рибомустина [5,6,[16][17][18]. Однако необ ходимо отметить высокую частоту нейтропении в на шем исследовании (III-IV степеней тяжести в 38 % случаев), значительно превышающую значения, пред ставленные итальянской группой исследователей (III-IV степеней тяжести в 14 % случаев) [5].…”
Section: Discussionunclassified
“…Их частота коррелировала с добавлением брентуксимаба ведотина к режиму BeGeV и составила 71 и 50 % соот ветственно. Согласно международным данным коли чество кожных реакций в исследовании режима BeGEV было 10 % [5,6], а при использовании режима BBVвозросло до 65 % [9]. Очевидно, что именно такая ком бинация потенцирует развитие подобного негемато логического осложнения.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…BEGEV (gemcitabine, vinorelbine, bendamustine, prednisone) has also shown very encouraging results as well with a reported CR rate of 75% and ORR of 83%. Nearly ninety percent of patients proceeded to ASCT with an impressive 5-year PFS estimate of 77%, ( Table 1 ) [ 23 , 24 ]. Furthermore, this regimen was well tolerated with grade 3 or higher adverse events limited mainly to hematologic toxicity (14%) and infection (7%).…”
Section: Approach To R/r Chl Following Front-line Therapymentioning
confidence: 99%